Evaluation and selection of anatomic sites for magnetic resonance imaging-guided mild hyperthermia therapy: a healthy volunteer study. (17th November 2018) - V. V. N. Kothapalli, Satya; Altman, Michael B.; Zhu, Lifei; Partanen, Ari; Cheng, Galen; Gach, H. Michael; Straube, William; Zoberi, Imran; Hallahan, Dennis E.; Chen, Hong
Abstract: Purpose: Since mild hyperthermia therapy (MHT) requires maintaining the temperature within a narrow window (e.g. 40–43 °C) for an extended duration (up to 1 h), accurate and precise temperature measurements are essential for ensuring safe and effective treatment. This study evaluated the precision and accuracy of MR thermometry in healthy volunteers at different anatomical sites for long scan times. Methods: A proton resonance frequency shift method was used for MR thermometry. Eight volunteers were subjected to a 5-min scanning protocol, targeting chest wall, bladder wall, and leg muscles. Six volunteers were subjected to a 30-min scanning protocol and three volunteers were subjected to a 60-min scanning protocol, both targeting the leg muscles. The precision and accuracy of the MR thermometry were quantified. Both the mean precision and accuracy <1 °C were used as criteria for acceptable thermometry. Results: Drift-corrected MR thermometry measurements based on 5-min scans of the chest wall, bladder wall, and leg muscles had accuracies of 1.41 ± 0.65, 1.86 ± 1.20, and 0.34 ± 0.44 °C, and precisions of 2.30 ± 1.21, 1.64 ± 0.56, and 0.48 ± 0.05 °C, respectively. Measurements based on 30-min scans of the leg muscles had accuracy and precision of 0.56 ± 0.05 °C and 0.42 ± 0.50 °C, respectively, while the 60-min scans had accuracy and precision of 0.49 ± 0.03 °C and 0.56 ± 0.05 °C, respectively. Conclusions: Respiration, cardiac, and digestive-related motion pose challenges to MR thermometry of the chest wall and bladder wall. The leg muscles had satisfactory temperature accuracy and precision per the chosen criteria. These results indicate that extremity locations may be preferable targets for MR-guided MHT using the existing MR thermometry technique.